Hiding in plain view: genetic profiling reveals decades old cross contamination of bladder cancer cell line KU7 with HeLa - Jäger, Wolfgang; Horiguchi, Yutaka; Shah, Jay; Hayashi, Tetsutaro; Awrey, Shannon; Gust, Kilian M.; Hadaschik, Boris; Matsui, Yoshiyuki; Anderson, Shawn; Bell, Robert H.; Ettinger, Susan; So, Alan I.; et al. (The journal of urology, 2013)
Purpose: - KU7 is a popular urothelial carcinoma cell line that was isolated from the bladder - of a patient at Keio University in 1980. It has subsequently been widely used in laboratories - around the world. We describe how routine cell line authentication revealed that KU7 - was cross contaminated almost 30 years ago with HeLa, a cervical carcinoma cell line. - - Materials and Methods: - Presumed KU7 clones dating from 1984 to 1999 were provided by M.D. Anderson Cancer - Center, Vancouver Prostate Centre, Kyoto University, Tokyo Medical University and - Keio University. HeLa was obtained from ATCC®. Genomic DNA was isolated and short - tandem repeat analysis was performed at the M.D. Anderson Cancer Center Characterized - Cell Line Core Facility, Johns Hopkins University Fragment Analysis Facility and RIKEN - BioResource Center, Ibaraki, Japan. Comparative genomic hybridization was performed - on a platform (Agilent Technologies, Santa Clara, California) at Vancouver Prostate - Centre. - - Results: - The short tandem repeat profile of all KU7 clones was an exact match with that of - HeLa. Comparative genomic hybridization of all samples revealed an abundance of shared - chromosomal aberrations. Slight differences in some genomic areas were explained by - genomic drift in different KU7 clones separated by many years. - - Conclusions: - Our analysis identified that cross contamination of KU7 with HeLa occurred before - 1984 at the source institution. All KU7 clones in the urological literature should - be considered HeLa and experimental results should be viewed in this light. Our results - emphasize the need to authenticate cell lines in oncological research.
Gesehen am 24.03.2021